A multiplex method for rapidly identifying viral protease inhibitors - Seo Jung Hong; Samuel J Resnick; Sho Iketani; Ji Won Cha; Benjamin Alexander Albert; Christopher T Fazekas; Ching-Wen Chang; Hengrui Liu; Shlomi Dagan; Michael R Abagyan; Pavla Fajtová; Bruce Culbertson; et al. (Molecular Systems Biology)
Abstract With current treatments addressing only a fraction of pathogens and new viral threats constantly evolving, there is a critical need to expand our existing therapeutic arsenal. To speed the rate of discovery and better prepare against future threats, we establish a high-throughput platform capable of screening compounds against 40 diverse viral proteases simultaneously. This multiplex approach is enabled by using cellular biosensors of viral protease activity combined with DNA-barcoding technology, as well as several design innovations that increase assay sensitivity and correct for plate-to-plate variation. Among >100,000 compound-target interactions explored within our initial screen, a series of broad-acting inhibitors against coronavirus proteases were uncovered and validated through orthogonal assays. A medicinal chemistry campaign was performed to improve one of the inhibitor’s potency while maintaining its broad activity. This work highlights the power of multiplex screening to efficiently explore chemical space at a fraction of the time and costs of previous approaches.